A single center experience of adrenalectomy for adrenal tumors - Seung Keon Shin; Jong-Min Park (Korean Journal of Clinical Oncology, 2017)
Purpose In this study, we reviewed 16 cases of adrenalectomy, focusing specifically on the surgical outcomes and clinical courses. Methods The data from 16 patients who underwent an adrenalectomy at our hospital between January 2007 to December 2016 were retrospectively analyzed based on their medical records. Data available for each patient included age, sex, tumor location, length of postoperative hospital stay, tumor size, tumor pathology, final diagnosis, operation time, operative blood loss, and type of operation. Results The study population consisted of eight males and eight females, with a mean age of 58.00±11.34 years (range, 33–76 years). The mean tumor size was 2.78±2.02 cm (range, 0.5–7 cm). Fourteen patients were diagnosed with functional adrenal tumors and two with nonfunctional adrenal tumors. Compared to laparoscopic adrenalectomy, open surgery resulted in a statistically significantly longer operating time, increased operative blood loss, and a longer postoperative hospital stay. Conclusion If the hormonal activity of adrenal tumors is not confirmed, the tumor should be considered functional when accompanied by related symptoms and an adrenalectomy should be performed. In addition, we suggest that a laparoscopic adrenalectomy is superior to an open adrenalectomy in terms of recovery after surgery, despite the small number of cases evaluated. Open adrenalectomy should be considered following comprehensive consideration of the patient’s condition, such as accompanying surgery or metastatic cancer.